Revised Bloom Taxonomy-Oriented Learning Activities to Develop Scientific Literacy and Creative Thinking Skills - Pujawan, I. G. N.; Rediani, N. N.; Antara, I. G. W. S.; Putri, N. N. C. A.; Bayu, G. W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Students’ literacy and creative thinking skills in the learning process are not optimal. Students only master science concepts without communicating and solving problems in everyday life. It happens because the learning activities applied by the teacher are less innovative and varied. This study aims to analyze the impact of revised Bloom’s Taxonomy-oriented learning activities on creative thinking skills and scientific literacy. The study had quasi-experimental in a pretest-posttest control group design. The sample of this study was 60 students; 30 students in the experimental class and 30 students in the control class. Data collection methods used were tests and questionnaires. The instrument used was a test instrument in description of 10 questions to test critical thinking skills, a questionnaire instrument consisting of 30 statements, and a questionnaire instrument to measure scientific literacy skills. Data analysis methods used were quantitative descriptive and inferential statistical. The Manova analysis obtained 0.00 0.05. Based on the analysis results, effective learning activities develop creative thinking skills and scientific literacy, either partially or simultaneously. Even though it affects creative thinking skills and scientific literacy, the strongly influenced variable is creative thinking skill, which is indicated by a significant increase in the mean value. Thus, learning activities based on Bloom’s Taxonomy become learning recommendations to develop creative thinking skills and scientific literacy.